(3TQM GdSfIs - (3CHh eMeO GdMSjf Hf eSYhO GdaQGA GdHZhis; (3GdHZhj , GdMSjf Hf eSYhO Hf eMeO GdaQGA, eMjj GdSfI CHh eMeO,J (B510 (3g` s ((3Ydi Hf EHQGgje Hf OGTe Hf CMeO Hf jhSa GdJHQjRi s)
(3ChdgG (B:s
(3HGH ef bUO eGd QLd Ch MQjeg bGd SeYJ GdfHi Udi Gddg Ydjg hSde jbhd (B:" (3ef bJd Ohf eGdg agh TgjO (B" (3gPG MOjK eJab Ydi UMJg s
(3BNQgG (B:s
(3HGH (B" (3dGjJfGLi EKfGf Ohf GdKGdK (B" (3bhdg (B: (3abgj Odjd Ydi Cf GdeSGQI ai GdLeY hMjK dGQjHI LGFRI , hGddg CYde s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs